Social Costs of the Inefficient Management of the EU Funds for Bulgaria - Shteryo Nozharov (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The study identifies and defines the social costs of the inefficient management of EU funds for Bulgaria. It is analyzed the last due programme period (2007-2015) and its prolongation. As methodology of the research the V4 BM model of Al-Debei and Avison (2010) which has not been used for analysis of EU funds management for cohesion policy in the public sector, is applied. In this way its potential for application in this field is tested. The concept of the study could be successfully used for analysis of the social costs of inefficient management of EU funds in other member-states.
Keywords: F15; H43; O21; 330; social costs; absorption of EU funds; V4 BM model